STUDI PERILAKU BERDASARKAN PENGARUH PARTISIPASI MASYARAKAT, KOMPETENSI APARATUR PENGELOLA DANA DESA DAN KOMITMEN ORGANISASI TERHADAP AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA - Tituk Diah Widajantie (BAJ: Behavioral Accounting Journal, 2021)
This study aims to identify, test and demonstrate the benefits of community involvement, the potential of regional financial management tools, and the commitment of the organization responsible for managing the APBD in Tarik Regency. This study includes several approaches. The population in this study resides in Tarik District and the surrounding villages. The Intentional Sampling method was used in the selection of the model by taking a sample of 96 participants. The theory was tested using a series of horizontal analysis methods, which previously tested positive data, static values, and static measurements using SPSS 24. The results showed that the diversity of community participation and the capacity of local government officials affected responsibility. regional financial management, if various institutional commitments do not affect regional financial management obligations.